How mitochondrial dysfunction affects zebrafish development and cardiovascular function: an in vivo model for testing mitochondria‐targeted drugs. (12th June 2013) - Pinho, Brígida R; Santos, Miguel M; Fonseca‐Silva, Anabela; Valentão, Patrícia; Andrade, Paula B; Oliveira, Jorge M A
<x xml:space="preserve">Abstract</x> Background and Purpose Mitochondria are a drug target in mitochondrial dysfunction diseases and in antiparasitic chemotherapy. While zebrafish is increasingly used as a biomedical model, its potential for mitochondrial research remains relatively unexplored. Here, we perform the first systematic analysis of how mitochondrial respiratory chain inhibitors affect zebrafish development and cardiovascular function, and assess multiple quinones, including ubiquinone mimetics idebenone and decylubiquinone, and the antimalarial atovaquone. Experimental Approach Zebrafish (Danio rerio) embryos were chronically and acutely exposed to mitochondrial inhibitors and quinone analogues. Concentration‐response curves, developmental and cardiovascular phenotyping were performed together with sequence analysis of inhibitor‐binding mitochondrial subunits in zebrafish versus mouse, human and parasites. Phenotype rescuing was assessed in co‐exposure assays. Key Results Complex I and II inhibitors induced developmental abnormalities, but their submaximal toxicity was not additive, suggesting active alternative pathways for complex III feeding. Complex III inhibitors evoked a direct normal‐to‐dead transition. ATP synthase inhibition arrested gastrulation. Menadione induced hypochromic anaemia when transiently present following primitive erythropoiesis. Atovaquone was over 1000‐fold less lethal in zebrafish than reported for Plasmodium falciparum, and its toxicity partly rescued by the ubiquinone precursor 4‐hydroxybenzoate. Idebenone and decylubiquinone delayed rotenone‐ but not myxothiazol‐ or antimycin‐evoked cardiac dysfunction. Conclusion and Implications This study characterizes pharmacologically induced mitochondrial dysfunction phenotypes in zebrafish, laying the foundation for comparison with future studies addressing mitochondrial dysfunction in this model organism. It has relevant implications for interpreting zebrafish disease models linked to complex I/II inhibition. Further, it evidences zebrafish's potential for in vivo efficacy or toxicity screening of ubiquinone analogues or antiparasitic mitochondria‐targeted drugs.